2015
DOI: 10.1016/j.arth.2014.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Pain Level and Patient Expectation Predict Hospital Length of Stay After Total Hip Arthroplasty

Abstract: a b s t r a c t a r t i c l e i n f oThe purpose of this study was to identify preoperative predictors of length of stay after primary total hip arthroplasty in a patient population reflecting current trends toward shorter hospitalization and using readily obtainable factors that do not require scoring systems. A retrospective review of 112 consecutive patients was performed. High preoperative pain level and patient expectation of discharge to extended care facilities (ECFs) were the only significant multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Halawi et al [ 17 ] retrospectively reviewed 112 consecutive patients who underwent total hip arthroplasty and found a significant association between PLOS and preoperative pain level. In this study, we analyzed the relationship between VAS pain score preoperatively and on POD1, POD3, and PLOS of TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Halawi et al [ 17 ] retrospectively reviewed 112 consecutive patients who underwent total hip arthroplasty and found a significant association between PLOS and preoperative pain level. In this study, we analyzed the relationship between VAS pain score preoperatively and on POD1, POD3, and PLOS of TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Although we anticipated seeing a reduction in LOS, we had expected the decrease to be more clinically meaningful. Other studies have shown that multiple factors may affect LOS, including patient expectations and care pathways [23], [24], [25]. Although our group took a significant effort into modifying the simple to make changes, such as PT staffing hours, we have lacked needed resources and institutional support to similarly improve the other components.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature suggests an association between expectation fulfillment and patient satisfaction. 5,[8][9][10][11][12][13][14][15][16][17][18] Further investigation is needed to determine whether setting realistic expectations prior to MMS can improve patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…7 Numerous studies from other surgical specialties have shown that patients are dissatisfied when their expectations do not match the actual outcome. 5,[8][9][10][11][12][13][14][15][16][17][18] Few studies have examined patient expectations for scarring after skin cancer surgery. 5 The primary objective of this study was to compare patients' and surgeons' preoperative estimations of scar length with actual scar length after MMS for facial skin cancers.…”
Section: Introductionmentioning
confidence: 99%